Towards Accurate Measurement of Computer Usage in a Rural Kiosk - Veeraraghavan, R.; Singh, G; Pitti, B.; Smith, G; Meyers, B.; Toyama, K.; Toyama, Kentaro; Meyers, Brian; Smith, Greg (Third International Conference on Innovative applications of Information Technology for Developing World - Asian Applied Computing Conference 2005, 2005)
Rural PC kiosks are increasingly seen as a tool for socio-economic development in developing countries. In order to make kiosks successful, it helps to understand patterns of usage in existing kiosks. Often, questionnaires or interviews are conducted to determine usage patterns, but self-reporting by subjects is notoriously inaccurate. In this paper, we present a tool that allows accurate measurement of when and how PCs in a kiosk are being used. We discuss how an existing tool has been adapted for easy data collection in rural kiosks and present evidence that even regular users of computers are poor at estimating their own usage statistics.